The Relevance Of Ethical Principles On The Quality Of Nigerian Tertiary Education - Kani, Umar Mohammed (2020)
The central purpose of this study is investigating the problem of quality in Nigerian tertiary education within the context of ethics, guided by pragmatism and utilitarianism, to theorise associated factors and offer suggestions from ethical perspectives for improvement. It followed from the perception of stakeholders and general public that quality of Nigeria’s tertiary education has declined and the problem has not been holistically researched from the ethical viewpoint. Being a philosophical study through empirical approach, philosophical and qualitative methods were employed.